Jacked pipes as retaining wall in underpass construction - Jaysankar, R. (2008)
Excavation of about 7 m depth under the Merdeka Bridge at the side of the Kallang River was carried out for the proposed underpass at the extension of Crawford Street in Singapore. The Merdeka Bridge which is part of the Nicoll Highway was opened to traffic throughout the construction of the proposed underpass. Since the construction was carried out under a very important structure and in poor ground conditions with thick soft clay layers of up to 40 m depth, a conservative and safe retaining system with staged excavation was adopted. An extensive and sound instrumentation scheme had been proposed and used for the monitoring of movements of the surrounding ground and Merdeka Bridge during the construction.